PENERAPAN PEMBELAJARAN KOOPERATIF TGT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS SISWA KELAS VIII SMP - Muzaemah, Muzaemah (LP3 Universitas Negeri Semarang, 2020)
Penggunaan metode yang kurang tepat dapat menimbulkan kebosanan sehingga siswa tidak termotivasi untuk belajar dan masih rendahnya hasil belajar IPS disebabkan masih dominannya skill menghafal daripada memproses. Tujuan Penelitian Tindakan Kelas untuk mengetahui bagaimana penerapan pembelajaran kooperatif tipe TGT atau Teams Games Tournament dapat meningkatkan motivasi dan hasil belajar IPS kelas VIIIG SMP Negeri 26 Purworejo tahun pelajaran 2017/2018. Penelitian dilaksanakan dalam 2 siklus, tiap siklus terbagi 3 kali pertemuan yang meliputi perencanaan, pelaksanaan, observasi dan refleksi. Hasil angket motivasi siklus I kepada diperoleh 21 atau 75% termotivasi , siklus II 25 atau 89% termotivasi, hasil belajar siklus I yang tuntas 16 atau 57,1 % belum tuntas 12 atau 42,9 %. Sedangkan siklus II siswa yang tuntas 24 atau 85,7% yang belum tuntas 4 atau 14,3%. Berdasarkan data siklus I dan II sangat signifikan adanya kepuasan siswa terhadap pembelajaran kooperatiftipe TGT.The use of inappropriate method can lead to boredom, and still low in Social learning results are caused by the still dominant skills of memorizing skills rather than processing their own understanding of a material.The aim of classroom action research is to know in two cycles how the application of cooperative learning model type TGT (Teams Games Tournament) can improve the motivation and learning 28 the students of outcomes IPS class VIIIG SMP Negeri of 26 Purworejo academic year 2017/2018. This study was conducted with 2 (two) cycles, each cycles is divided into three (3) consisting of planning, implementation, observation and reflection. From the result of motivation questionnaire in the first cycle to 28 students, 17 students 60,7%) were highly motivated. While in the second cycle obtained the results of the questionnaire of motivation 24 (85,7%) have been highly motivated. From posttest in cycle I with KKM score 74, is 64,3% (18 students) and got score below is 10 students (36,7%). While the results of postest cycle II, It is proved that the students who got the complete score is 25 students (89,3%), and the unfinished 3 students (10,7%).Based on the data of motivation and learning result from cycle I and cycle II are very significant and There is students' satisfaction on cooperative learning TGT type.